THE LANGUAGE OF THE “SECRET SENSE”: ON THE LINGUISTIC STUDY OF PROPRIOCEPTION - Alexandra V. Nagornaya (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The paper considers the possibility of linguistic research into proprioception – the perception of the body boundaries, its position, balance and movement in space. The study of proprioception is presented as part of the general paradigm of Sensory Linguistics and is regarded as one of its main priorities. Starting from the classical definition of proprioception as a “secret sense” proposed by Ch. Sherrington, the author identifies the factors that impede its cognitive processing, verbalization and scientific analysis. The paper describes the phenomenological properties of proprioception as a pre-reflexive bodily experience, substantiates the need for its differentiation from interoception, demonstrates its role in the formation of subjective experience, analyzes different approaches to its definition within natural sciences and arts. It further looks into the inner form of the term “proprioception” to reveal a link between this type of sensory experience, the formation of identity and the normal mode of human functioning as an integral bodily and spiritual being. The paper proposes a few lines of linguistic research into proprioception. Among them are the inventory of proprioceptive terminology, the analysis of semantic features and functions of perceptonyms, research into metaphor as the key means of conceptualizing proprioceptive experience, and the study of syntactic structures used in verbalizing proprioceptive sensations.